EALÁT. Reindeer Herders Voice: Reindeer Herding, Traditional Knowledge and Adaptation to Climate Change and Loss of Grazing Lands. - Oskal, Anders; Turi, Johan Mathis; Mathiesen, Svein D.; Burgess, Philip (International Centre for Reindeer Husbandry, 2009)
This book is a two years middle term report from a Norwegian information project in the Arctic Council entitled EALÁT. The term «ealát» is from the language of the indigenous Sámi people of Fennoscandia, and means «good pasture». This word is related to the term «eallu», which means «herd» and the origin of these terms derives from the word «eallin», or «life». In other words, pastures are the foundation for the reindeer herd, and reindeer herds are the foundation for the lives of reindeer herding peoples. Reindeer herding is the primary livelihood for over 20 indigenous peoples throughout the circumpolar North, with a remarkably similar organisation wherever it is found. In all, nearly 100,000 people are involved in herding approximately 2,5 million domesticated reindeer in 9 national states. Reindeer herding can be seen as a human-coupled ecosystem with a historically high resilience to climate variability and change, and a circumpolar model for sustainable management of the marginal areas of the North. Indigenous peoples in the Arctic now face major challenges related to changes in their societies, globalisation and a changing climate. EALÁT has therefore been initiated by the Association of World Reindeer Herders (WRH) to address the challenges of climate change and loss of pastures, in order to maintain and develop robust reindeer herding societies for the future. The project is endorsed by the Sustainable Development Working Group (SDWG) of the Arctic Council, with the full title «SDWG EALÁTInformation: Reindeer herding, traditional knowledge and adaptation to climate change and loss of pastures». This is an information project focusing on climate change, loss of pastures and how the traditional knowledge of reindeer herders themselves can be utilized to adapt to these changes. The aim is to build capacity and competence for adaptation in local reindeer herding communities, as well as to increase knowledge on these issues for national authorities, the Arctic Council system, industrial developers, and mainstream societies in the North. EALÁT-Information is also a part of the IPY EALÁT-Network Study1, a broader consortium endorsed by the International Polar Year which focuses on the vulnerability of reindeer herding to climate change.